Preparation and Characterization of Carbamazepine Cocrystal in Polymer Solution - Hao Zhang; Ying Zhu; Ning Qiao; Yang Chen; Linghuan Gao (MDPI AG, 2017)
In this study, we attempted to prepare carbamazepine (CBZ) cocrystal through the solution method in ethanol-water solvent mixture (volume ratio 1:1) and polyvinyl pyrrolidone (PVP) solution. Nicotinamide (NIC) and saccharin (SAC) were selected as cocrystal coformers. Cocrystal screening products were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Powder X-ray Diffraction (PXRD) techniques. Characterization results show that in ethanol-water solvent mixture, pure CBZ-NIC cocrystal can be prepared, while CBZ-SAC cocrystal cannot be obtained. The addition of PVP can inhibit CBZ-NIC cocrystal formation and facilitate CBZ-SAC cocrystal formation.